Improvement of the classification system for wheelchair rugby: athlete priorities - Altmann, V. C.; Hart, A. L.; van Limbeek, J.; Vanlandewijck, Y. (Adapted Physical Activity Quarterly, 2014)
A representative sample (N = 302) of the wheelchair rugby population responded to a survey about the classification system based on prioritized items by International Wheelchair Rugby Federation members. Respondents stated, "The classification system is accurate but needs adjustments" (56%), "Any athlete with tetraequivalent impairment should be allowed to compete" (72%), "Athletes with cerebral palsy and other coordination impairments should be classified with a system different than the current one" (75%), and "The maximal value for trunk should be increased from 1.0 to 1.5" (67%). A minority stated, "Wheelchair rugby should only be open to spinal cord injury and other neurological conditions" (36%) and "There should be a 4.0 class" (33%). Results strongly indicated that athletes and stakeholders want adjustments to the classification system in two areas: a focus on evaluation of athletes with impairments other than loss of muscle power caused by spinal cord injury and changes in classification of trunk impairment.